Pengaruh Persepsi Kemudahan, Kegunaan Dan Kepercayaan Terhadap Minat Menggunakan Gopay : Studi Kasus Di Karawang - Setiawan, Maman Nur; Solihin , Agung (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2023)
This study aims to determine the effect of perceived convenience, perceived usefulness and perceived trust on interest in using gopay in 2023. The type of data used is quantitative descriptive data. The data used is primary data obtained from distributing questionnaires to Karawang residents. The population in this study were residents in Karawang, while the sampling technique used accidental sampling, namely determining the sample based on chance so that 100 respondents were obtained